Deviation compensation in LPBF series production via statistical predeformation and structural pattern analysis - Philipp Lechner; Christoph Hartmann; Daniel Wolf; Abdelrahman Habiba (Journal of Intelligent Manufacturing, 2023)
Abstract This article proposes two approaches for a tailored geometrical deviation compensation for Laser-Powder-Bed-Fusion production. The deviation compensation is performed by a non-rigid deformation of the manufacturing geometry in each iteration to reduce the geometrical deviations from the target geometry. It is important for geometric compensation approaches to separate deterministic deviations from random scatter, since compensating scatter can result in unstable behaviour. In order to compensate only deterministic deviations two novel approaches for a local estimation of the scatter are successfully introduced and tested using a hybrid model of a series production cycle.
Keywords: 330; Selective laser melting; Additive manufacturing; Series production; LPBF; Preforming; Predeformation; Geometrical deviation compensation